2008
DOI: 10.1037/0003-066x.63.3.182
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, followership, and evolution: Some lessons from the past.

Abstract: This article analyzes the topic of leadership from an evolutionary perspective and proposes three conclusions that are not part of mainstream theory. First, leading and following are strategies that evolved for solving social coordination problems in ancestral environments, including in particular the problems of group movement, intragroup peacekeeping, and intergroup competition. Second, the relationship between leaders and followers is inherently ambivalent because of the potential for exploitation of follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
570
2
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 615 publications
(622 citation statements)
references
References 160 publications
15
570
2
10
Order By: Relevance
“…We list the most important of these schools given that we used them to estimate their impact on citations of quantitative articles. Relying on previous reviews (Bass & Bass, 2008;Gardner, Lowe, Moss, Mahoney, & Cogliser, 2010;House & Aditya, 1997;Lowe & Gardner, 2000;Van Seters & Field, 1990), Day and Antonakis (2012) classified leadership schools into the following parsimonious categories: (a) trait, focusing on stable and personal attributes (e.g., personality) of leaders (Judge, Bono, Ilies, & Gerhardt, 2002;Lord, De Vader, & Alliger, 1986); (b) behavioral, which studies behavioral styles of leaders, usually looking at social support (consideration) or task (initiating structure) orientation (Judge, Piccolo, & Ilies, 2004), or other behavioral aspects of leadership; (c) contextual, which models how context affects the leadership phenomenon (Liden & Antonakis, 2009;Osborn, Hunt, & Jauch, 2002;Porter & McLaughlin, 2006); (d) contingency, which seeks to model how situational demands affect the impact of behavioral styles on outcomes (Fiedler, 1967;House & Mitchell, 1974); (e) relational, which focuses on quality of relations between leaders and followers (Dansereau, Graen, & Haga, 1975;Graen & Uhl-bien, 1995); (f) information processing, which employs a cognitive perspective of leadership (Lord, Foti, & De Vader, 1984;Lord & Maher, 1991); (g) the "new" leadership, which focuses on visionary, values-centered, and charismatic aspects of leadership and related perspectives (Bass, 1985;House, 1977); (h) biological and evolutionary perspectives, which take a genetic, neuroscientific, "hard"-science, or evolutionary approach to leadership (Van Vugt, Hogan, & Kaiser, 2008;Waldman, Balthazard, & Peterson, 2011). They also defined the "skeptics" school, which treats leadership as a social construction (Eden & Leviatan, 1975;Meindl, Ehrlich, & Dukerich, 1985), though they have suggested that this school is mostly subsumed in the information processing perspective.…”
Section: Mode Of Inquirymentioning
confidence: 99%
“…We list the most important of these schools given that we used them to estimate their impact on citations of quantitative articles. Relying on previous reviews (Bass & Bass, 2008;Gardner, Lowe, Moss, Mahoney, & Cogliser, 2010;House & Aditya, 1997;Lowe & Gardner, 2000;Van Seters & Field, 1990), Day and Antonakis (2012) classified leadership schools into the following parsimonious categories: (a) trait, focusing on stable and personal attributes (e.g., personality) of leaders (Judge, Bono, Ilies, & Gerhardt, 2002;Lord, De Vader, & Alliger, 1986); (b) behavioral, which studies behavioral styles of leaders, usually looking at social support (consideration) or task (initiating structure) orientation (Judge, Piccolo, & Ilies, 2004), or other behavioral aspects of leadership; (c) contextual, which models how context affects the leadership phenomenon (Liden & Antonakis, 2009;Osborn, Hunt, & Jauch, 2002;Porter & McLaughlin, 2006); (d) contingency, which seeks to model how situational demands affect the impact of behavioral styles on outcomes (Fiedler, 1967;House & Mitchell, 1974); (e) relational, which focuses on quality of relations between leaders and followers (Dansereau, Graen, & Haga, 1975;Graen & Uhl-bien, 1995); (f) information processing, which employs a cognitive perspective of leadership (Lord, Foti, & De Vader, 1984;Lord & Maher, 1991); (g) the "new" leadership, which focuses on visionary, values-centered, and charismatic aspects of leadership and related perspectives (Bass, 1985;House, 1977); (h) biological and evolutionary perspectives, which take a genetic, neuroscientific, "hard"-science, or evolutionary approach to leadership (Van Vugt, Hogan, & Kaiser, 2008;Waldman, Balthazard, & Peterson, 2011). They also defined the "skeptics" school, which treats leadership as a social construction (Eden & Leviatan, 1975;Meindl, Ehrlich, & Dukerich, 1985), though they have suggested that this school is mostly subsumed in the information processing perspective.…”
Section: Mode Of Inquirymentioning
confidence: 99%
“…One can draw attention to two distinct evolutionary features in human beings that are relevant to this connection. The first is that throughout history, human beings have instinctively been social animals (Van Vugt, Hogan and Kaiser 2008). This instinct has first created pack leaders and in accordance with our increasing intelligence and more complex culture, this instinct reasonably led first to chieftains and medicine men and then to kings and hypothetical gods.…”
Section: Discussionmentioning
confidence: 99%
“…An open question is why individuals would not all attempt to perform the role associated with the highest fitness benefit, or in other words, why individuals would perform roles that put their genes at an evolutionary disadvantage for survival. Group selection pressures among human tribes have been proposed as one possible explanation for the evolution of leaders and followers [4]. In this paper, we explore whether group selection is sufficient to produce division of labor, where individual selection rewards different roles unequally.…”
Section: Introductionmentioning
confidence: 99%
“…For example, leadership is a common role found within multiple species, where the benefits of leadership are significantly greater than that of a follower. In human societies, leaders of organizations commonly earn many times more than the average worker [4]. An open question is why individuals would not all attempt to perform the role associated with the highest fitness benefit, or in other words, why individuals would perform roles that put their genes at an evolutionary disadvantage for survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation